Influence Organisational Culture, Leadership Style, and Discipline Toward Performance Lecturer with Motivation as Mediation - Yusuf, Muhammad (Letiges, 2024)
Understanding the influence of organizational culture, leadership style, and discipline on lecturer performance can provide deeper insight into improving lecturer performance and the quality of education at regional private universities. This research aims to analyze the impact of organizational culture, leadership style and discipline on the performance of lecturers at private universities in South Sulawesi while identifying motivation as a mediator between the independent and dependent variables. This study applies a survey approach and regression analysis in quantitative research methodology, using Structural Equation Modeling (SEM) to analyze the connections between independent variables, intervening variables, and dependent variables. The SEM analysis results reveal that culture organization has a positive impact on lecturer motivation. However, there is no significant influence on their performance. Additionally, leadership style temporarily has a negative and significant influence on lecturer motivation without a substantial effect on performance. While discipline has no direct impact on performance, it contributes optimistically to motivation. Motivation plays a crucial role as a mediator between independent and dependent variables, indicating that enhancing culture organization, leadership style, and discipline can increase motivation and lecturer performance in the region. The limitations of this research focus are limited to private educational institutions in South Sulawesi, as well as the limitations of the SEM model and data, emphasizing the necessity of advanced studies with broader coverage and diverse data collection methods. Understanding the relationship between the influence of organizational culture, leadership style and discipline on lecturer performance is expected to provide deeper insight into improving lecturer performance and the quality of education offered at private universities in the region.